Sensitivity analysis on river discharge from uncertainties in basin and rainfall parameters - Toh, Amos Yu Heng (2016)
This report in summary describes the analysis of the sensitivity of basin drainage to basin parameters for the River Ciliwung, in the city of Jakarta. By using the hydrological routing method of the HEC-HMS (Hydrologic Engineering Centre – Hydrologic Modelling System) software, runoff discharge can be generated by the events-process models. The model takes into account for the temporal and spatial distribution of the drainage runoff. Various parameters were considered for the variation in the sensitivity analysis. The parameters to be varied included the roughness index and the landuse percentage (rural grasslands vs urban concrete areas). The rainfall input used is pre-generated by 23 years of annual rainfall and converted to the Log Pearson Type 3 distribution. The baseline model parameters are also calibrated by a historical large flood –The 2007 flood event. The results show the capabilities of the software and the influence on the range of the discharge at the Mangarai and Depok Junction and their respective stage levels of the river. A change in 20% of the landuse can increase the peak discharge by at least 80m3/s which represent a great percentage increase from the baseline. It depicts a huge increase in the runoff amount. Furthermore, the decrease in roughness index can also increase the peak discharge of about 10% and the stage level of the river by about 3%. Lastly, the discharge at the Ciliwung Mouth was converted into financial losses using an existing model. By this conversion, the discharge data is then used with possible levee plans to generate the financial losses that each levee plans may develop. This allows sensitivity in financial losses to be also evaluated. However, this work is also not without limitations as more parameter can be included in the investigations in the future and using more than one station of rainfall data. All in all, the study shows the potential effects of a single parameter variation and how the local authorities would be able to apply the results into the disaster mitigation and flood control especially so for the economically active city of Jakarta.